2003
DOI: 10.1037/0021-9010.88.6.1019
|View full text |Cite
|
Sign up to set email alerts
|

A Lengthy Look at the Daily Grind: Time Series Analysis of Events, Mood, Stress, and Satisfaction.

Abstract: The present study investigated processes by which job stress and satisfaction unfold over time by examining the relations between daily stressful events, mood, and these variables. Using a Web-based daily survey of stressor events, perceived strain, mood, and job satisfaction completed by 14 university workers, 1,060 occasions of data were collected. Transfer function analysis, a multivariate version of time series analysis, was used to examine the data for relationships among the measured variables after fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(154 citation statements)
references
References 67 publications
4
148
0
2
Order By: Relevance
“…Because stressful work conditions often lead to impaired mood (Fuller et al, 2003), mood repair is one of the core functions of recovery. Research on mood regulation identified a range of different strategies individuals pursue to improve their mood including both cognitive and behavioral approaches (Parkinson, Totterdell, Briner, & Reynolds, 1996;Thayer, Newman, & McClain, 1994).…”
Section: Conceptualizations Of Recoverymentioning
confidence: 99%
“…Because stressful work conditions often lead to impaired mood (Fuller et al, 2003), mood repair is one of the core functions of recovery. Research on mood regulation identified a range of different strategies individuals pursue to improve their mood including both cognitive and behavioral approaches (Parkinson, Totterdell, Briner, & Reynolds, 1996;Thayer, Newman, & McClain, 1994).…”
Section: Conceptualizations Of Recoverymentioning
confidence: 99%
“…Similarly, sport and related activities have been identified as a powerful mood regulation strategy (Larsen & Prizmic, 2004;Thayer, 1987). Therefore, because the experience of job stressors is associated with mood impairment (Fuller et al, 2003;Zohar et al, 2003), one would assume that, after stressful days, people would want to engage in sport activities that promote recovery and improve mood. However, many people's everyday experience and the limited-resources model of self-regulation (Muraven & Baumeister, 2000) suggest that this is often not the case.…”
Section: Job Stressorsmentioning
confidence: 99%
“…In line with this everyday experience, there is convincing empirical evidence for these fluctuations. Examples include studies on a person's affective state Zohar, Tzischinski, & Epstein, 2003), experiences such as work engagement and vigor (Sonnentag, 2003;Xanthopoulou, Bakker, Demerouti, & Schaufeli, 2009), or work behavior such as creativity at work (Amabile, Barsade, Mueller, & Staw, 2005;Ohly & Fritz, in press) and job performance (Binnewies, Sonnentag, & Mojza, 2009;Fuller et al, 2003). Diary designs offer means of analyzing such fluctuating data.…”
Section: What Are Diary Studies?mentioning
confidence: 99%
“…For example, Rook and Zijlstra (2006) have demonstrated that weekday fatigue scores as well as sleep quality follow a specific pattern. Grech et al (2009) examined how fatigue develops over the course of several consecutive shifts during navy patrols (see also Fuller et al, 2003).…”
Section: Diary Study Design and Types Of Research Questions Addressedmentioning
confidence: 99%